Relação entre concepção e manejo docente da agressividade discente na educação infantil - Oliveira, Andréa Pires de (2018)
This study aimed to analyze the link between teachers’ conceptions about childhood aggressivity and their pedagogic handling in Preschool, in the context of daily relationships between seven nursery/kindergarten teachers and their children, in a public Preschool facility of João Pessoa’s metropolitan area. The principal reference used for the data analysis was D. W. Winnicot’s theory about childhood aggressivity and the environmental function, which can be favorable or complicate for the aggressivity integration by the child. When entering Preschool this child will need to continue the emotional development process, reason why the investigation of that relation is fundamental, justifying this study. In the literature review, dialoguing with Educational Cultural Studies authors, concerning the hybridity of the educational and school field, it was proposed a reflection about the Psychoanalysis’ contributions to the Education field. The hypothesis of an existent relation between conceptions and teacher’s childhood aggressivity management was investigated to solve the problem about the existence of this relation and the characteristics of its terms. As a qualitative study, it was developed a case study with the triangulation of three data groups, collected by observations, individual interviews and speech registered in focus groups. Seven Nursery teachers, during three months, on morning and evening shifts, collaborated with the research, providing data witch were analyzed in two times: at first, the articulation of observation and half structured individual interviews has evidenced that teachers’ conceptions about childhood aggressivity had influence on their management, commending it. Consisting of, mainly, common sense, these conceptions confirmed interventions, mostly, exclusively punitive of the children’s aggressivity expressions. Once this relation was established by the researcher, at the second part of the study, the relation between conception and teacher’s management was confirmed through the reflections made by the participants about their pedagogical practice on the focus group. On both parts of the study, researcher and teachers, with different analysis levels, verified the need of a proper mediation of childhood aggressivity. The teachers’ biography, reveling their subjective difficulties to deal with their own unconscious aggressivity, helped the understanding of their difficulties to welcome and manage well enough the children’s aggressivity, whose child integration of it, in an analysis based on Winnicot theory, was frustrated. This has pointed to the necessity of a teacher’s qualification that consider the subjectivity of the Childhood Education professionals, aiming to promote now relational arrangements between teacher and child, luckily supporting the teacher’s management quality before this phenomenon.